Material transshipment for precast fabrication - Ko, Chien-Ho (Journal of Civil Engineering and Management, 2013)
Materials required for precast fabrication are dissimilar to those cast at construction sites. Fabricators who lack materials must wait until specific suppliers deliver the required materials. The objective of this study is to reduce total material management costs in the supply chain system through the most advantageous transshipment strategies. A material supply chain framework that enables fabricators to implement lateral transshipment is first proposed. Transshipment strategies are then formulated into a mathematical model. The most advantageous transshipment strategies are analyzed using computer simulation. Diverse order lead times, demands, transportation costs, and shortage costs are simulated to approximate operational conditions encountered in supply chain systems. Through various experiments, the most advantageous strategy for precast fabrication industry can be found. In addition, four rules are developed based on simulation results to enhance transshipment decision making. This research is one of the pioneering studies applying lateral transshipment to precast production management.